Moral Distress Reconsidered - McCarthy, Joan (Nursing ethics, 2008)
Moral distress has received much attention in the international nursing literature in recent years. In this article, we describe the evolution of the concept of moral distress among nursing theorists from its initial delineation by the philosopher Jameton to its subsequent deployment as an umbrella concept describing the impact of moral constraints on health professionals and the patients for whom they care. The article raises worries about the way in which the concept of moral distress has been portrayed in some nursing research and expresses concern about the fact that research, so far, has been largely confined to determining the prevalence of experiences of moral distress among nurses. We conclude by proposing a reconsideration, possible reconstruction and multidisciplinary approach to understanding the experiences of all health professionals who have to make difficult moral judgements and decisions in complex situations.